1996
DOI: 10.1139/y96-051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the estrous cycle on the sensitivity to catecholamines in right atria from rats submitted to foot-shock stress

Abstract: We investigated the mechanisms of the alterations in sensitivity to catecholamines in right atria from female rats exhibiting regular 4-day estrous cycles after three foot-shock sessions at estrus, metestrus, and diestrus or at diestrus, proestrus, and estrus. Right atria from stressed rats sacrificed at diestrus showed subsensitivity to noradrenaline and adrenaline. After in vitro sympathetic denervation (38 microM 6-hydroxydopamine) plus inhibition of neuronal reuptake (0.1 microM desipramine) subsensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…Because we have previously shown that after this same stress protocol cardiac tissue and adipocytes are supersensitive to isoproterenol and subsensitive to noradrenaline (7,8) and to BRL 37344 (8), we examined the effect of an infusion of these compounds on plasma glucose, glycerol and triacylglycerol levels in stressed rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because we have previously shown that after this same stress protocol cardiac tissue and adipocytes are supersensitive to isoproterenol and subsensitive to noradrenaline (7,8) and to BRL 37344 (8), we examined the effect of an infusion of these compounds on plasma glucose, glycerol and triacylglycerol levels in stressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues from stressed rats are supersensitive to adrenaline (2,7), which is elevated in stressed rats, and to isoproterenol (7). However, subsensitivity to noradrenaline has been reported in cardiac tissue and adipocytes from stressed rats (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations